High-temperature thermal barrier-coated Sylramic-iBN/pyrolytic carbon/chemical vapor infiltration silicon carbide ceramic matrix composite behavior in a combustion environment. (April 2018) - Sabelkin, V; Zawada, L; Mall, S; Bertrand, D; Przybyla, CP
An environmental barrier-coated Sylramic-iBN/pyrolytic carbon/chemical vapor infiltration silicon carbide ceramic matrix composite was characterized in a harsh combustion environment under two conditions; (i) with a coating surface temperature of 1480℃, and (ii) with a combustion flame distance of 120 mm (constant flux). Three coating systems were evaluated; Coating "A" (ytterbium silicate using hafnium–silicate bond), Coating "B" (ytterbium silicate using alumina bond), and Coating "C" (ytterbium–silica compounds using alumina bond). All three coatings survived with essentially no mass loss up to 25 h when tested at 1480℃. At a flame distance of 120 mm coatings "A" and "B" experienced extensive degradation and strength loss while coating "C" had practically no degradation in retained strength. Coating "C" outperformed the other two coatings exposed to the harsh combustion environment. It performed best in terms of material loss, thermal barrier capability, and residual tensile strength.